Pengaruh Analisis Fundamental, Teknikal dan Bandarmologi terhadap Harga Saham Syariah yang Terdaftar di Jakarta Islamic Index Periode 2018-2021 - Namashuda, Fajrika; Rosmanidar, Elyanti; Rahma, Sri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Equity-based sharia stocks that comply with Islamic principles. One of the sharia stock indices is the Jakarta Islamic Index (JII). JII is an index consisting of the 30 most liquid Islamic stocks on the IDX which was launched in 2000. To select 30 Islamic stocks to be included in the index calculation, there are additional criteria carried out by IDX, namely liquidity criteria. The liquidity indicators used are based on market capitalization and daily transaction value. Usually calculated based on the last one year period and every day there must always be transactions. This study uses a quantitative descriptive research method, namely research that emphasizes the analysis of numerical data processed by statistical models. This method is called the quantitative method because the research data uses numbers that indicate the value of the observation variable that leads to a certain time period. This research results that from the results of the t test table it is known that the fundamental analysis variables partially influence the prices of Islamic stocks listed on the Jakarta Islamic Index (JII) in 2018-2021. From the results of the t test table it is known that the technical analysis variable has a partial effect on the prices of Islamic stocks listed on the Jakarta Islamic Index (JII) for 2018-2021. From the results of the t test table it is known that the bandarmological analysis variable has a partial effect on the prices of Islamic stocks listed on the Jakarta Islamic Index (JII) for 2018-2021. From the results of the f test table it is known that the variables of fundamental analysis, technical analysis, and bandarmological analysis simultaneously influence the prices of Islamic stocks listed on the Jakarta Islamic Index (JII) for 2018-2021. Keywords: Fundamental Analysis, Technical, Bandarmology, Sharia Stocks, Sharia Market